БНХАУ, Монгол Улсыг төмөр замаар холбох бодлого, үйл явцад хийсэн дүн шинжилгээ (Journal of International Studies, 2014)
English title: Analysis on policies of linking Mongolia and the People’s Republic of China with railway and its process